Application of Next Generation Sequencing for personalized medicine for sudden cardiac death - Morini, Elena; Sangiuolo, Federica; Caporossi, Daniela; Novelli, Giuseppe; Amati, Francesca (Frontiers in Genetics, 2015)
Abstract Sudden cardiac death (SCD) is a serious public health problem. In the United States, more than 300,000 people are affected by SCD every year. Significantly, sudden deaths represent 20% of the total mortality and 50% of cardiovascular mortality in Western countries. In addition, SCD constitutes one of the most important unsolved challenges in the practice of forensic pathology because of the failure to determine the exact cause of sudden death. In young individuals, SCD is frequently caused by cardiomyopathies and channelopathies, that have generally an autosomal dominant pattern of inheritance. The impact of genetics and genetic testing on the clinical management of these diseases is unquestioned. In particular, genetic tests are an important tool for identifying pre-symptomatic individuals carrying genetic variant that predisposes them to sudden cardiac death. High-throughput sequencing technologies offer novel opportunities to deeper investigate the genetic background underlying these fatal diseases and to early identify individuals at risk for SCD. In this review, we provide an overview of the development of Next-Generation Sequencing (NGS) technologies and of guidelines useful to design an efficient sequencing protocol and to perform an accurate data analysis. We suggest a flow chart to follow for the set up of a genetic screening protocol for the prevention of cardiac pathologies, in particular SCD events, in young athletes.